Respuesta :

Answer:

D) [tex]4*ln(2)[/tex]

Step-by-step explanation:

Find the inverse function of f(x):

[tex]f(x)=log_2(2x)[/tex]

[tex]y=log_2(2x)[/tex]

[tex]x=log_2(2y)[/tex]

[tex]2^x=2y[/tex]

[tex]2^{x-1}=y[/tex]

[tex]f^{-1}(x)=2^{x-1}[/tex]

Take the derivative of the inverse function:

[tex]\frac{d}{dx}(f^{-1}(x))[/tex]

[tex]\frac{d}{dx}(2^{x-1})[/tex]

[tex]\frac{d}{dx}(e^{(x-1)(ln2)})[/tex] <-- Logarithmic Differentiation

[tex]ln(2)*e^{(x-1)(ln(2))[/tex]

[tex]ln(2)*2^{x-1}[/tex]

Substitute x=3:

[tex]ln(2)*2^{3-1}[/tex]

[tex]ln(2)*2^2[/tex]

[tex]4*ln(2)[/tex]